EMPIRICAL STUDY: LEADERSHIP, ORGANIZATION CULTURE, EMPLOYEE ENGAGEMENT IN INFORMATION TECHNOLOGY CONTINUOUS IMPROVEMENT ADOPTION: Received: 10th May 2023; Revised: 26th September 2023, 25th October 2023; Accepted: 01st November 2023 - Reddy Akepati, Suresh Kumar; Seetharaman, Arumugam; Maddulety, K.; Gururajan, Raj (PEOPLE: International Journal of Social Sciences, 2023)
Continuous Improvements (CI) is well-known for its significance in driving and facilitating process and products improvements in organizations. For decades, large organizations used CI to improve and streamline process and workforce. CI thinking and adoption is critical for IT functions to improve aspects such as innovation, team productivity, service reliability, and cost optimization. The role of organization culture, leadership, employee engagement become key for adoption of CI to ensure stability, scalability, and sustainability to business functions through right tools, technologies, and services. There is need for research on the influence of trio on adoption of CI in the context of IT. The trio are interrelated components that play a crucial role in the success and sustainability of any organization. The aim of this study is to evaluate these three factors, its influence on adoption of CI by IT function using a quantitative approach. This study engages IT stakeholders from ITES, global companies which have their global IT development centres in India to ascertain their views. The finding of the study shows organization culture has a strong influence on adoption of CI in IT. This study can provide critical insights to management in streamlining IT practice, design organization mechanisms for better adoption of CI in IT.